Characterizing of functional human coding RNA editing from evolutionary, structural, and dynamic perspectives. Issue 11 (3rd September 2014) - Solomon, Oz; Bazak, Lily; Levanon, Erez Y.; Amariglio, Ninette; Unger, Ron; Rechavi, Gideon; Eyal, Eran
ABSTRACT A‐to‐I RNA editing has been recently shown to be a widespread phenomenon with millions of sites spread in the human transcriptome. However, only few are known to be located in coding sequences and modify the amino acid sequence of the protein product. Here, we used high‐throughput data, variant prediction tools, and protein structural information in order to find structural and functional preferences for coding RNA editing. We show that RNA editing has a unique pattern of amino acid changes characterized by enriched stop‐to‐tryptophan changes, positive‐to‐neutral and neutral‐to‐positive charge changes. RNA editing tends to have stronger structural effect than equivalent A‐to‐G SNPs but weaker effect than random A‐to‐G mutagenesis events. Sites edited at low level tend to be located at conserved positions with stronger predicted deleterious effect on proteins comparing to sites edited at high frequencies. Lowly edited sites tend to destabilize the protein structure and affect amino acids with larger number of intra‐molecular contacts. Still, some highly edited sites are predicted also to prominently affect structure and tend to be located at critical positions of the protein matrix and are likely to be functionally important. Using our pipeline, we identify and discuss several novel putative functional coding changing editing sites in the genes COPA (I164V), GIPC1 (T62A), ZN358 (K382R), and CCNI (R75G). Proteins 2014; 82:3117–3131. © 2014 Wiley Periodicals, Inc.